2023
DOI: 10.1111/beer.12586
|View full text |Cite
|
Sign up to set email alerts
|

Women and CSR budgeting and spending: Does ownership enhance their CSR role?

Saeed Rabea Baatwah,
Effiezal Aswadi Abdul Wahab

Abstract: We investigate the impact of women shareholders on corporate social responsibility (CSR) and how they interact with women directors to exert a greater influence on CSR activities. Little is known about how women's ownership can enhance their roles in CSR practices. Based on data from Omani‐listed firms during 2016–2020 and using CSR budgeting and spending as proxies for CSR activities, firms with women shareholders allocate more CSR budgeting and spend more money on CSR activities. However, we also find that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
(281 reference statements)
0
1
0
Order By: Relevance
“…With the increasing proportion of female executives in publicly traded companies across various industries, many scholars have shifted their focus to women in corporate governance research. Regarding the impact of female executives on CSR, some research findings suggest that companies with female executives perform better in areas such as charitable donations [24]. Other studies have found that female executives lack the professional knowledge to improve enterprise innovation because they are more cautious about taking strategic risks, which suppresses innovation activities and restricts the expenditure of CSR [25].…”
Section: Female Participation In Managementmentioning
confidence: 99%
“…With the increasing proportion of female executives in publicly traded companies across various industries, many scholars have shifted their focus to women in corporate governance research. Regarding the impact of female executives on CSR, some research findings suggest that companies with female executives perform better in areas such as charitable donations [24]. Other studies have found that female executives lack the professional knowledge to improve enterprise innovation because they are more cautious about taking strategic risks, which suppresses innovation activities and restricts the expenditure of CSR [25].…”
Section: Female Participation In Managementmentioning
confidence: 99%